Light-induced reactions of methionine and riboflavin in model wine: Effects of hydrolysable tannins and sulfur dioxide. (15th November 2019) - Fracassetti, Daniela; Limbo, Sara; Pellegrino, Luisa; Tirelli, Antonio
Highlights: Photo-oxidation of riboflavin and methionine was investigated in model wine. Hydrolysable tannins and sulfur dioxide were studied to limit the photo-oxidation. Methionine degradation increased as its concentration increased. Higher volatile sulfur compounds were found in anoxic condition. Hydrolysable tannins limited methionine degradation and light struck-taste. Abstract: The riboflavin-mediated photo-degradation of methionine in white wine has been related to onset of undesired light-struck taste. This research investigated the effects of different concentrations of riboflavin and methionine, hydrolysable tannins from various sources (nut galls, chestnut and oak woods) and sulfur dioxide on methionine degradation in a model wine exposed to light. Increased methionine concentration resulted in its increased degradation with the consequent formation of volatile sulfur compounds, namely methanethiol, dimethyl disulphide and dimethyl trisulphide. Tannins, especially nut gall tannin, were effective in limiting both methionine degradation and the production of volatile sulfur compounds. Sulfur dioxide enhanced the methionine degradation although the light-struck taste was not perceived when sulfur dioxide concentration was higher than 50 mg/L. In conclusion, the use of hydrolysable tannins can represent a promising tool for protecting white wine against the light-struck taste also limiting the use of sulfur dioxide.